Quadruplex-Forming Motif Inserted into 3'UTR of Ty1his3-AI Retrotransposon Inhibits Retrotransposition in Yeast - Tokan, Viktor; Rodriguez Lorenzo, Jose Luis; Jedlicka, Pavel; Kejnovska, Iva; Hobza, Roman; Kejnovsky, Eduard (Biology, 2021)
Guanine quadruplexes (G4s) serve as regulators of replication, recombination and gene expression. G4 motifs have been recently identified in LTR retrotransposons, but their role in the retrotransposon life-cycle is yet to be understood. Therefore, we inserted G4s into the 3'UTR of Ty1his3-AI retrotransposon and measured the frequency of retrotransposition in yeast strains BY4741, Y00509 (without Pif1 helicase) and with G4-stabilization by N-methyl mesoporphyrin IX (NMM) treatment. We evaluated the impact of G4s on mRNA levels by RT-qPCR and products of reverse transcription by Southern blot analysis. We found that the presence of G4 inhibited Ty1his3-AI retrotransposition. The effect was stronger when G4s were on a transcription template strand which leads to reverse transcription interruption. Both NMM and Pif1p deficiency reduced the retrotransposition irrespective of the presence of a G4 motif in the Ty1his3-AI element. Quantity of mRNA and products of reverse transcription did not fully explain the impact of G4s on Ty1his3-AI retrotransposition indicating that G4s probably affect some other steps of the retrotransposon life-cycle (e.g., translation, VLP formation, integration). Our results suggest that G4 DNA conformation can tune the activity of mobile genetic elements that in turn contribute to shaping the eukaryotic genomes.
Keywords: retrotransposition; Pif1 helicase; G-quadruplex; yeast; Ty1 LTR retrotransposon; N-methyl mesoporphyrin (NMM)